2017
DOI: 10.1128/aem.02361-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Phosphatase Enzyme Potentially Involved in the Sugar Phosphate Stress Response in Pseudomonas fluorescens

Abstract: The alginate-producing bacterium Pseudomonas fluorescens utilizes the Entner-Doudoroff (ED) and pentose phosphate (PP) pathways to metabolize fructose, since the upper part of its Embden-Meyerhof-Parnas pathway is defective. Our previous study indicated that perturbation of the central carbon metabolism by diminishing glucose-6-phosphate dehydrogenase activity could lead to sugar phosphate stress when P. fluorescens was cultivated on fructose. In the present study, we demonstrate that PFLU2693, annotated as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…However, the data may also reflect a preference of the organism to internalize then further metabolize F-6-P. These parameters, including V max and K m , are also in line with what has been reported for other members of the HAD family phosphatases in bacteria (5,21,24).…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the data may also reflect a preference of the organism to internalize then further metabolize F-6-P. These parameters, including V max and K m , are also in line with what has been reported for other members of the HAD family phosphatases in bacteria (5,21,24).…”
Section: Figsupporting
confidence: 90%
“…number of mechanisms have been proposed to contribute to sugar-phosphate stress, as follows: (i) futile cycling, in which the cells expend energy to internalize and phosphorylate the sugar, but the sugar is then dephosphorylated and expelled (5); (ii) reduction of essential metabolic intermediates arising from an inability to internalize other carbohydrates (6); (iii) creation of toxic metabolic by-products, such as methylglyoxal (7,8); or (iv) deleterious effects of specific sugar-phosphates that act as allosteric modifiers of enzymes or regulatory proteins, causing dysregulation of metabolism (9). The majority of research on sugar-phosphate stress has been conducted with Gramnegative model organisms, with far fewer studies carried out with known pathogens or Gram-positive bacteria (10).…”
mentioning
confidence: 99%
“…Our earlier studies in P. fluorescens indicated that even in a mucA mutant, alginate biosynthesis does not start immediately after the first alginate biosynthetic complexes have been assembled (Maleki et al, 2016). Moreover, both the P. fluorescens transposon insertion study (Ertesvåg et al, 2017) and studies focusing on the synthesis of fructose 6-phosphate (Maleki et al, 2015(Maleki et al, , 2017 clearly indicated that the cells prioritize growth and survival over alginate production. The present study indicates that the same is true for A. vinelandii.…”
Section: Alginate Biosynthesis Seems To Be Regulated By the Metabolicmentioning
confidence: 99%
“…In order to optimize bacterial production processes, it is important to understand how alginate biosynthesis is regulated as well as elucidate which other metabolic aspects have an influence on production levels. The precursor for the alginate monomers is fructose 6-phosphate, so alginate biosynthesis is closely connected to the central carbohydrate metabolism of the cells (Maleki et al, 2015(Maleki et al, , 2017Ertesvåg et al, 2017). Alginate production is furthermore an energy demanding process and is tightly controlled by a complex network of regulators which also influence other cellular processes (Urtuvia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the course of model reconstruction, GSMM for P. putida Kt2440 was chosen as the basis as both P. putida Kt2440 and P. fluorescens use Entner–Doudoroff (ED) pathway for glycolysis . When catechol was selected as the substrate, both strains take β‐ketoadipate route for catechol degradation .
…”
Section: Methodsmentioning
confidence: 99%